Designs and Parameters of Compact One-Chain Power Transmission Lines with Con-centric Location of Phases’ Wires - G. I. Seliverstov; A. V. Komar; Yu. N. Petrenko (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
New power lines of concentric designs with improved electrical parameters are proposed. In these power lines natural power of one voltage class is directly proportional to the number of drives in a split-phase and doesn’t almost depend on wire size ling and the distance between approximated wires of opposite phases. Lines of different voltage classes with the same number of wires in a split-phase have practically equal values of the equivalent parameters – inductance, capacitance and wave resistance.The system of wires transposition is offered, which provides the same load of wire lines and allows the intermediate power selection at any line point and its entirety.